Effect of Lampaya medicinalis Phil. (Verbenaceae) and Palmitic Acid on Insulin Signaling and Inflammatory Marker Expression in Human Adipocytes - Gabriela Yuri; Mariana Cifuentes; Pedro Cisternas; Adrián Paredes; Paulina Ormazabal (MDPI AG, 2024)
Background: Aging and obesity are associated with insulin resistance (IR) and low-grade inflammation. Molecularly, IR is characterized by a reduction in glucose uptake and insulin signaling (IRS-1/Akt/AS160 pathway), while inflammation may result from upregulated NF-κB pathway after low Tyr-IκBα phosphorylation. Upregulated phosphatase activity of PTP1B is associated with impaired insulin signaling and increased inflammation. Plasma levels of palmitic acid (PA) are elevated in obesity, triggering inflammation and disruption of insulin signaling. Traditional medicine in Northern Chile uses oral infusions of Lampaya medicinalis Phil. (Verbenaceae) to treat inflammatory conditions. Significant amounts of flavonoids are found in the hydroethanolic extract of Lampaya (HEL), which may account for its biological activity. The aim of this work was to study the effect of HEL and PA on insulin signaling and glucose uptake as well as inflammatory marker expression in human adipocytes. Methods: We studied HEL effects on PA-induced impairment on insulin signaling, glucose uptake and inflammatory marker content in human SW872 adipocytes. HEL cytotoxicity was assessed in adipocytes at different concentrations (0.01 to 10 g/mL). Adipocytes were incubated or not with PA (0.4 mM, 24 h) with or without HEL (2 h pre-incubation), and then stimulated with insulin (10 min, 100 mM) or a vehicle. Phospho-IRS-1, phospho-Akt, phospho-AS160, phospho-NF-κB and phospho-IκBα, as well as protein levels of PTP1B, were assessed using Western blotting, and glucose uptake was evaluated using the 2-NBDG analogue. Results: At the assessed HEL concentrations, no cytotoxic effects were observed. PA decreased insulin-stimulated phospho-Akt and glucose uptake, while co-treatment with HEL increased such markers. PA decreased phospho-IRS-1 and phospho-Tyr-IκBα. On the other hand, incubation with HEL+PA decreased phospho-AS160 and phospho-NF-κB compared with cells treated with PA alone. Conclusion: Our results suggest a beneficial effect of HEL by improving PA-induced impairment on molecular markers of insulin signaling, glucose uptake and inflammation in adipocytes. Further studies are necessary to elucidate whether lampaya may constitute a preventive strategy for people whose circulating PA levels contribute to IR and inflammation during aging and obesity.